Comparative analysis of four cleaning methods of endodontic files - Bárbara Guandalini; Ivana Vendramini; Denise Piotto Leonardi; Flávia Sens Fagundes Tomazinho1; Paulo Henrique Tomazinho (Revista Sul-Brasileira de Odontologia, 2015)
Due to the size and design of endodontic files, these instruments have been considered one of the most difficult to clean among all dental instruments. The debris maintenance within the sulcus prevents the effective sterilization and may compromise the disinfection of root canal systems in endodontic therapy. However, there is neither a method nor technique that standardized the cleaning of these instruments. Objective: To evaluate the cleaning ability of four techniques used in dentistry. Material and methods: For this purpose, 30 new size #40 Flexofile were used for the preparation of the canals of mandibular molars of pigs. After instrumentation, the contamination and the presence of debris in the sulcus was confirmed and the files were randomly divided into four groups: control group (without cleaning), group 1 (enzymatic detergent + manual brushing with nylon bristle brush), group 2 (ultrasound + enzymatic detergent), group 3 (ultrasound + water) and group 4 (gauze embedded in 70% alcohol). Next, all files were photographed and photographs were printed at high quality. The spirals containing debris were counted. Results: Manual cleaning with enzymatic detergent and nylon bristle brush, ultrasound with either water or detergent showed the best cleaning capacity in which respectively 100%, 98.9% and 96.2%, of the spirals were free of debris. Cleaning with alcohol and gauze proved to be ineffective, showing debris in more than 40% of the spirals by visual analysis. In control group, 91% of the spirals presented debris. It can be concluded that the association between manual and ultrasound cleaning may be promising in ensuring a cleaning protocol for endodontic files cleaning.